EFL PRE-SERVICE TEACHERS' REFLECTION: A CASE STUDY IN AN INDONESIAN INSTRUCTIONAL CONTEXT - Nurfaidah, Sitti (2016)
Reflective teaching practice, a popular instructional practice in current second/foreign language teacher education and teacher professional development program, is widely believed to be able to help bridge the gap between a teacher's belief and classroom practices. Despite the fact that reflective teaching practices have been of importance in western academic contexts, they have not been realized as one of important parts in eastern instructional contexts. In an attempt to alleviate the scarcity of such empirical study in Indonesian instructional settings, this research was conducted. This thesis delineates a case study investigating the development of reflection of Indonesian EFL pre-service teachers during a field experience. Four EFL pre-service teachers enrolled in a 45-school-day field teaching practice volunteered to participate. Data gathered through reflective teaching journals and stimulated recalls were used as the main source. Meanwhile, observations through videotaped lessons were used to develop further investigation during stimulated recall protocols, and transcripts from interviews were used to enrich the participants' profile. Data were then analysed using the content analysis technique and constant comparison pertaining to conceptual and analytical frameworks used. The findings indicated that the EFL pre-service teachers maintained elements of reflective practice as the five elements of reflection appeared in their teaching journals as well as revealed in their reflections during interviews and stimulated recalls. The most frequently occurring elements were suggestions and problems. In terms of levels of reflection, mostly the participants showed their ability to reflect within the range of Low Level (Level 3) and Moderate Level (Level 4) of dialogic reflection. No one, however, indicated the quality of critical reflection since this level requires more teaching experiences and time exposure. Further examination focused on concerns or issues of reflection as discussed in their data revealed that the pre-service teachers' concerns were unique to each participant but mainly focused on learning management, classroom management, knowledge management, and language management. This study proposes that in order the reflective phase be implemented in a full cycle with more exploration of the second phase, the pre-service teachers should be exposed to sound knowledge-base in ELT, sufficient classroom observations and classroom teaching experiences, which would eventually lead to a quality level of reflection aiming to critical reflection. This study implies that reflective learning and reflective teaching should be systematically integrated within courses of teacher education program.;--- Pengajaran reflektif, suatu praktek mengajar yang dikenal luas dalam program pendidikan guru bahasa asing dan pengembangan profesional guru masa kini, dipercaya oleh banyak pihak mampu menjembatani jurang antara keyakinan guru dan praktek nyata di dalam kelas. Kendati pengajaran reflektif telah menjadi bagian penting dari pengajaran dalam konteks akademik barat, akan tetapi tidak demikian halnya dalam konteks akademik timur. Sebagai upaya mengisi kekurangan studi empiris terkait di Indonesia, maka penelitian ini dilakukan. Disertasi ini menyajikan suatu studi kasus yang meneliti perkembangan refleksi mahasiswa Indonesia selama mereka melakukan praktek mengajar lapangan. Sebanyak empat mahasiswa Pendidikan Bahasa Inggris yang sedang mengikuti program praktek mengajar lapangan selama 45 hari sekolah menjadi partisipan secara sukarela. Data yang diperoleh melalui jurnal mengajar reflektif dan stimulated recall menjadi sumber data utama, sedangkan data yang diperoleh melalui observasi dengan cara merekam proses mengajar digunakan untuk mengembangkan investigasi dalam stimulated recall. Disamping itu, transkrip wawancara digunakan untuk memperkaya profil partisipan. Data yang diperoleh dianalisis dengan cara tehnik analisis isi dan perbandingan terus-menerus berdasarkan kerangka konseptual dan analitis acuan. Hasil temuan menunjukkan bahwa kelima elemen refleksi muncul dalam proses releksi mereka seperti yang terungkap melalui jurnal mengajar dan selama stimulated recall serta wawancara berlangsung. Elemen refleksi yang paling sering mucul adalah suggestions dan problem. Terkait level refleksi, hampir semua partisipan menunjukkan kemampuan refleksi pada rentang Level Rendah (Level 3) dan Level Sedang (Level 4) pada refleksi dialogis, dan tidak satu pun yang menunjukkan kualitas refleksi kritis mengingat level ini menuntut pengalaman mengajar yang lebih banyak dan waktu paparan mengajar yang lebih lama. Penelitian lebih lanjut terhadap isu yang menjadi perhatian mereka dalam refleksi mengungkapkan bahwa eksplorasi isu unik pada tiap partisipan tetapi utamanya terpusat pada manajemen pembelajaran, manajemen kelas, manajemen pengetahuan, dan manajemen bahasa. Penelitian ini menyarankan bahwa agar tahapan reflektif bisa dilakukan secara penuh dengan ekplorasi mendalam terhadap fase kedua refleksi, mahasiswa perlu diberi paparan terhadap pengetahuan belajar mengajar bahasa Inggris yang memadai, kesempatan lebih untuk melaksanakan observasi kelas dan pengalaman mengajar, yang mampu membawa mereka pada refleksi kritis. Penelitian ini menyiratkan bahwa pembelajaran reflektif dan pengajaran reflektif harus terintegrasi secara sistematis di dalam mata kuliah pada program pendidikan guru.